The Implementation of Bahasa Inggris Pemula In Enhancing Students’ Vocabulary Mastery Improving - Mira Mail; Husnani Aliah; Puspa Sari (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study was to determine the increase in vocabulary of class XI students through the implementation of bahasa inggris pemula applications at SMK Negeri 4 Palopo City, with a quantitative approach and a single group pretest posttest type of research. The data analysis technique used in this study is the t test. The results showed that the significance value of the t-test was less than 0.05, namely 0.000, and the t-count results were greater than t-table, namely t-count with a value of 5.080, which was greater than the t-table value of 2.093. Thus it was concluded that there was an effect of using Bahasa Inggris Pemula applications on the level of students' English vocabulary mastery.